THE ROLE OF PHYSICAL EDUCATION IN FORMING A HEALTHY LIFESTYLE - Nazarov , Sherzod; Maksimova , Nataliya (Effective scientific journals, 2025)
A healthy lifestyle is one of the most important conditions for the sustainable development of society and the well-being of individuals. In modern conditions of rapid technological development, urbanization, and sedentary behavior, the level of physical activity among children, adolescents, and adults is significantly decreasing. This situation leads to the growth of chronic non-communicable diseases, weakening of physical fitness, and deterioration of mental health. Physical education plays a key role in forming stable healthy lifestyle habits from an early age. This article examines the theoretical foundations of physical education, its influence on physical, mental, and social health, and its role in shaping healthy lifestyle behaviors. Using a systematic analytical approach, modern scientific views, pedagogical mechanisms, and international experiences are analyzed. The results show that regular physical education not only strengthens physical health but also forms discipline, motivation, social activity, and resistance to harmful habits. The study substantiates the necessity of strengthening the role of physical education in educational institutions and society as a whole.